الاستصحاب وأثره في الحكم القضائي مع تطبيقات قضائية في محاكم المملكة العربية السعودية - العمر، عبدالعزيز بن محمد بن علي (جامعة الحديدة - كلية التربية بالحديدة, 2024)
تناولت في هذا البحث التعريف بالاستصحاب وهو أحد الأدلة المختلف فيها بين المذاهب الأربعة حيث أن النزاع قائم في ثبوت حجيته مع بيان الراجح في حجيته من عدمها، ثم في تقسيمه وأنواعه وما يصلح للاحتجاج به وما لا يصلح للاحتجاج به، ثم ببيان شروط الاحتجاج والقواعد الفقهية المندرجة تحت هذا الدليل وبيان أثر هذا الدليل في الحكم القضائي حيث أنه من أولى الأدلة المتبادرة إلى الذهن في النزاعات والخصومات مع تطبيقات قضائية في المحاكم السعودية. In this research, I dealt with the definition of istihab, which is one of the evidences in which there is disagreement between the four schools of thought, as the dispute exists in proving its validity with a statement of what is more likely to be valid or not, then in its division, types, and what is suitable to be used as evidence and what is not suitable to be used as evidence, then with a statement of the conditions for protest and the jurisprudential rules that are included. Under this guide and explaining the impact of this evidence on judicial ruling, as it is one of the first pieces of evidence that come to mind in disputes and disputes with judicial applications in Saudi courts.
Keywords: الأحكام القضائية -- القواعد الفقهية -- النصوص الشرعية -- المحاكم السعودية